Aaron Douglas and Katherine Dunham: The Exploration and Legitimization of African and African Diasporic Roots. Issue 3 (2nd September 2017) - Johnson, Deborah; Oliver, Wendy
ABSTRACT: Aaron Douglas and Katherine Dunham were pioneers in setting a definitive course for African American artistic expression in the first half of the twentieth century. Their innovative positions revolved around the reclamation and integration of African and African diasporic sources into their work, which established the foundation for a new respect for African cultural inheritance. The two artists pursued this goal through their individual research and artistic inclinations and via an important link between them: the African American philosopher Alain Locke. Locke called for the theoretical foundation for the reclamation of African heritage and for its proud embrace. He knew the works of Douglas and Dunham well, and laid the groundwork for their lifelong focus on African heritage. Douglas and Dunham brought Locke's words to life through art, fulfilling a common mutually reinforcing mission.